Survival rate of melanoma patients based on selected morphological features - Niziołek, Aleksandra; Gertig, Grzegorz; Bręborowicz, Jan; Grodecka-Gazdecka, Sylwia (Contemporary Oncology/Współczesna Onkologia, 1999)
The aim of this report was to evaluate results of our surgical treatment of skin melanomas. For the study we used archival histopathological specimens of 120 patient operated in the Surgery Ward of the Oncological Chair of the Karol Marcinkowski University of Medical Sciences in Poznań. The specimens were stained with H+E and were described in terms of: the thickness of melanoma (measured by Breslow method), depth of invasion (according to Clark), mitosis number, intensification of lymphocyte infiltration, and the presence of regression symptoms or ulceration. This data was confronted with clinical data, taking into consideration the patients’ sex and the location of primary tumours. This in turn was compared with the survival rate, in particular for tumours <1,7 mm thick. The results obtained point to the need of cooperation between surgical oncologist and pathologist in predicting the rate of survival.